2016
DOI: 10.1007/s00535-016-1260-7
|View full text |Cite|
|
Sign up to set email alerts
|

A double-blind placebo controlled study of acotiamide hydrochloride for efficacy on gastrointestinal motility of patients with functional dyspepsia

Abstract: Our placebo-controlled study demonstrated that acotiamide significantly increased both gastric accommodation and gastric emptying in Japanese FD patients. Acotiamide also improved the patients' dyspeptic symptoms and anxiety score. Clinical Trials Registry no: UMIN000013544.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 39 publications
2
34
0
1
Order By: Relevance
“…However, Kusunoki et al used the same dosage as used in the current study and found a significant increase in expansion rate of the proximal stomach of FD patients after 14‐18 days of acotimaide treatment using untrasonography . In addition, Nakamura et al reported an increase in gastric accommodation in FD patients after 2 weeks of acotiamide treatment (100 mg tid) Based on these results, it is more likely that the study population plays a role in the discripancies found, and that our results again support the hypothesis that acotiamide does not affect non‐dysfunctional gastric functions, but can only improve impaired gastric functions. Another assumption could be that there is a ceiling effect for gastric accommodation assessed as a drop in IGP, and that the relaxatory function of the proximal stomach upon meal ingestion cannot be further enhanced in healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, Kusunoki et al used the same dosage as used in the current study and found a significant increase in expansion rate of the proximal stomach of FD patients after 14‐18 days of acotimaide treatment using untrasonography . In addition, Nakamura et al reported an increase in gastric accommodation in FD patients after 2 weeks of acotiamide treatment (100 mg tid) Based on these results, it is more likely that the study population plays a role in the discripancies found, and that our results again support the hypothesis that acotiamide does not affect non‐dysfunctional gastric functions, but can only improve impaired gastric functions. Another assumption could be that there is a ceiling effect for gastric accommodation assessed as a drop in IGP, and that the relaxatory function of the proximal stomach upon meal ingestion cannot be further enhanced in healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
“…These results were reproduced in several physiological clinical studies in FD patients, showing an improvement of gastric accommodation and gastric emptying rate following acotiamide treatment using scintigraphy, ultrasonography or barostat. 15,19,20 Moreover, acotiamide improved FD symptoms after two or more weeks of treatment in comparison to placebo 14,[20][21][22] and was shown to be more effective in the treatment of PDS than EPS. 8 Mechanistic studies in healthy subjects are limited.…”
Section: Introductionmentioning
confidence: 97%
“…Functional dyspepsia (FD) is a common disorder that is characterized by chronic or recurrent upper abdominal pain or discomfort without evidence of structural disease . Although the pathogenesis of FD remains largely unknown, various mechanisms such as genetic factors, impaired gastric motility, increased exposure of the duodenum to acid, visceral hypersensitivity, and altered brain‐gut duodenal axis interactions have been implicated . Low‐grade duodenal inflammation has recently been considered as a component of FD pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the intercellular acetylcholine concentration, acotiamide improves gastrointestinal motility. In clinical studies, 28,30 acotiamide was shown to significantly improve FD symptoms compared with placebo, with a particular effect on PDS symptoms. However, because these studies excluded patients with heartburn, it remains unknown whether acotiamide is effective in improving GERDrelated symptoms.…”
Section: Discussionmentioning
confidence: 99%